Prevalence of Academic Burnout in Higher Education Students and its Relationship with Study Habits (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This study examined the prevalence of academic burnout among higher education students and explored its relationship with study habits. A sample of 300 students completed the Maslach Burnout Inventory–Student Survey and the Study Habits Inventory. Results showed that 26% of students reported high burnout levels, while 47% experienced moderate burnout. A significant negative correlation was found between study habits and burnout (r = -0.61, p = 0.001), indicating that students with stronger study habits experienced lower burnout. The study highlights the importance of effective study behaviours as protective factors against burnout. Findings may inform educational policies, counselling interventions, and academic‑support programmes.